Neonatal death : any role for development interventions? - Nasreen, Hashima-E (Research and Evaluation Division, Brac, 2019)
Objective: The study aimed to explore whether or not the women focused development nterventions have any effect on neonatal death. Vlethods: The qualitative research method was used. Case study of cases (died within 28 days) and controls (live children and taken from the nearest door of cases) who born juring the year 1999-2000 was the main method employed. ICDDR, B surveillance jatabase provided the sampling frame. Results: The antenatal care of mothers and maternal nutrition carried out an important role in reducing neonatal death. On the other hand, physical abuse and emotional stress, and congenital anomalies are associated with increased risk of neonatal death. It is noted that women who were members of any government and non-government organization including BRAC were better exposed to antenatal care and nutrition as well as have had less physical abuse or emotional stress. Nevertheless, the study did not find any effect of mother's reproductive history, and birthing and newborn care on neonatal death. Conclusion: Regular medical check-up, following rules and regulations of antenatal care as well as the development intervention may have an influence over reduced trend of neonatal death over the year. In order to prove this hypothesis, a quantitative study, such as, a nested case-control study can be perfonned. To address whether or not BRAC's interventions have any influence, the study may, therefore, be perfonned in both BRAC and non-BRAC area.